Clinical features as predictors of bacteraemia in febrile children - Ankit Dashore; Ankush Jain; Navneet Khandelwal (International Journal of Health and Clinical Research, 2021)
Objective: To determine the prevalence, clinical features and various risk factors of bacteraemia among hospitalized febrile children aged between 3 months to 36 months, in a tertiary care center. Methods A cross-sectional, non-interventional, observational study consisting of 88 cases were included in our study and evaluated for the determination of prevalence of bacteraemia and its clinical correlates. Clinical Examination was then carried out and temperature, weight, length, clinical state, respiratory rate, heart rate was recorded. Yale score was assessed at time of admission and recorded. It is composed of 6 clinical parameters i.e. Quality of cry, Reaction to parent, State variation, Colour, Hydration & Social response. Results Among these, blood culture was positive in 24 cases, while in 64 cases blood culture showed no growth of any pathogenic organism. Staphylococcus aureus was one of the most common pathogenic organism (25%) seen among febrile children. Conclusion Empiric antibiotic therapy must include anti-Staphylococcal antibiotic in our setting in a febrile child without apparent focus of infection. Vaccination has a definite protective role and incomplete vaccination status of a child can be regarded as a strong predictor of presence of bacteraemia.